2001
DOI: 10.1590/s0100-879x2001000400009
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of age, resting heart rate and sedentary life style in short-term analysis of heart rate variability

Abstract: In order to assess the relative influence of age, resting heart rate (HR) and sedentary life style, heart rate variability (HRV) was studied in two different groups. The young group (YG) consisted of 9 sedentary subjects aged 15 to 20 years (YG-S) and of 9 nonsedentary volunteers (YG-NS) also aged 15 to 20. The elderly sedentary group (ESG) consisted of 16 sedentary subjects aged 39 to 82 years. HRV was assessed using a short-term procedure (5 min). R-R variability was calculated in the time-domain by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 39 publications
5
39
0
12
Order By: Relevance
“…This finding was similar to several published studies that evaluated healthy subjects at similar age ranges to the ones in the present work 2,4,6,15,29 . However, better aerobic fitness values were not effective in attenuating the reduction in HRV with age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was similar to several published studies that evaluated healthy subjects at similar age ranges to the ones in the present work 2,4,6,15,29 . However, better aerobic fitness values were not effective in attenuating the reduction in HRV with age.…”
Section: Discussionsupporting
confidence: 93%
“…Migliaro et al 29 found similar results to those of the present study, as they did not find significant differences in resting HRV between young sedentary and non-sedentary individuals. Evaluating the effect of a short-duration aerobic training program of mild to moderate intensity on heart rate variability in middle-aged individuals (40-60 years), Smith 15 found no alteration in HRV indices, although he showed improvement in aerobic fitness.…”
Section: Discussionsupporting
confidence: 91%
“…The trained individuals in the study of Melanson and Freedson [21] had significantly lower LF compared with their sedentary counterparts. Migliaro et al [22] found no differences in HRV (as determined from spectral analysis: LF and HF) parameters between sedentary (n = 29; 15-24 years) and non-sedentary (n = 29, 15-24 years) young people. The finding of higher HF power and HFnu in our study is supported by several cross-sectional studies [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…[16] Limitations to the present study are that the sample it is based on : [11] a) does not include a comparison group, e.g., unhealthy persons, to see if there was a difference in RPR between healthy and unhealthy persons. However, other studies indicate that persons at greater risk of an adverse clinical outcome do indeed tend to have different (higher) RPRs compared to their healthier counterparts; [4][5][6] b) applies to RPR that is obtained with the methodology used in the reference data (e.g., RPR in the seated position preceded by 4 minutes of seated rest); and c) is from the U.S. On this latter limitation, the author is not aware of substantive differences that might exist between same races from different countries. Thus, the results may be generalize-able to same races in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] A variety of health care providers use RPR including nurses, physicians, and chiropractors. Among the reasons nurses obtain RPR data are: a) to document the patient's pulse at admission for baseline, and b) to monitor any changes in RPR that may occur.…”
Section: Introductionmentioning
confidence: 99%